2015
DOI: 10.5455/umj.201506181158472
|View full text |Cite
|
Sign up to set email alerts
|

Hypernatremic Dehydration in Newborn Infants: A Review

Abstract: Background: Hypernatremic dehydration is a lethal condition in neonate which adversely affects central nervous system. Important causes of this condition in neonate are vomiting, diarrhea, improper preparation of infant formula, inadequate breast feeding and diabetes insipidus. Hypernatremic dehydration presents usually around tenth postnatal day. Clinical presentation is variable. Some present with lethargy; others are alert and hungry. Some are dehydrated whereas other are apparently hydrated. Treatment of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
1
8
1
7
Order By: Relevance
“…Jagdishet.al in Turkish province found that 5.6% neonates experience serum sodium concentrations of more than 145 mmol/L in hypernatremia dehydration [6], while our study shows that 29.8% of the infants have serum sodium levels lower than 135 mmol/L in hyponatremic dehydration. Clinical management of hyponatremia depends on treating the fundamental causes however precise assurance of etiology of hyponatremia is not known, additionally, a clinical history might be hard to get because of pediatric population.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Jagdishet.al in Turkish province found that 5.6% neonates experience serum sodium concentrations of more than 145 mmol/L in hypernatremia dehydration [6], while our study shows that 29.8% of the infants have serum sodium levels lower than 135 mmol/L in hyponatremic dehydration. Clinical management of hyponatremia depends on treating the fundamental causes however precise assurance of etiology of hyponatremia is not known, additionally, a clinical history might be hard to get because of pediatric population.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, emesis is also an important factor contributing to the fluid loss from the body resulting in electrolyte imbalance. As shown in our study, emesis and diarrhoea leads to hypokalemia as well in few subjects [6]. To tackle this, we need to monitor potassium levels in conjunction with sodium levels.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…hypernatremic dehydration in infancy is a medical emergency with high rates of mortality and morbidity. 8 Early diagnosis and prompt treatment is crucial for survival and better prognosis. Mother should be educated about signs and symptoms of dehydration before discharge after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical symptoms of hypernatremic infants include jaundice, hyperthermia, lethargy, restlessness, mucosal dryness and weight loss of more than 10% (11). In the case of delayed treatment of these infants, serious complications such as seizure, cerebral edema, renal failure and even death may occur (12,13). The follow-up of these infants has shown prolonged neurological complications in severe cases (1).…”
Section: Introductionmentioning
confidence: 99%